PENENTUAN RUMUS TINGGI BADAN BERDASARKAN PANJANG JEJAK KAKI PADA ETNIS JAWA - Marsa, Mardhatillah; Nurhantari, Yudha; Budiharjo, Santosa (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 8 No 1 (2018): Indonesian Journal of Legal and Forensic Sciences, 2018)
Background : Proof of footprints in forensic identification can be used in the determination of personal identification, for example the height. Estimated the height is done by measuring the length of footprints. Based on the literature, height was correlates directly with long bones. Footprints are made by the soles of the feet that are part of the long bones. The calculation of the height is more accurate using the formula derived from the population concerned so that testing needs to be done on each population. Objective : To find out whether there is a correlation between the length of the footprint of a person's height, especially the Javanese ethnic population and determine the estimation formula of height based on the length of the footprint. Methods : The study subjects consisted of 100 men and 100 Javanese ethnic women aged 21-30 years who were taken by consecutive sampling technique. Measurements were made by measuring subject height and footprint imprint then calculated each of the length of right and left footprints. Result : The average height of male Javanese ethnic is 172,36 cm and woman 158,45 cm. The average length of right and left footprints in males is 23,02 cm and female 22 cm. Pearson correlation test on all subjects had r value of 0.968 for right footprint and r 0.967 for left footprint. On the male subject has r value 0.908 for right foot print and r 0.902 for left footprint. In the female subject has r value 0.927 for the right foot print and r 0.931 for the left footprint. Conclusion : There is a strong relationship between the length of a person's footprint with height and this study has earned a formula of height estimation based on the length of the footprint on the Javanese. Keywords : height, footprint, identification, Javanese  ethnics